Functionality of Prosopis juliflora gum in the preparation of mango (Mangifera indica L.) nectar of low calorie content - González, Suhail; CastroWuilkermanÂ´s; Rincón, Fernando; Beltrán, Olga; Bríñez, Wilfido (Rev. Téc. Fac. Ing. Univ. Zulia)
Prosopis juliflora “cují”, species widely disseminated in Venezuela, produces seed gum. The behavior of this hydrocolloid in preparation of fruit nectars of low caloric content was studied. Six treatments, using different gum concentrations (0.10; 0.15; 0.20; 0.25 and 0.30%) and a control treatment (without gum), were carry out. The physicochemical characteristics (pH, °Brix, viscosity, turbidity), sensory (appearance, flavor, texture) of the elaborated product, were determinate. An experimental totally randomized design was applied. The comparison of the averages was made using Tukey”™s method, with a significance level of (p <0.05), there was used the procedure GLM of the statistical package SAS. The results obtained showed that, the soluble solid (°Brix), increased as increase the concentration of the (gum). The control treatment, presented a significant decrease (p <0.05) in the values of soluble solid during the storage. The viscosity exhibited by the nectar elaborated using the highest gum concentration (0.30%), was increase significantly (p <0.05), compared to the values observed for the control treatment (product without gum), and with the products prepared with the minor concentrations of gum. There were significant differences (p <0.05) in the values of turbidity of prepared nectars of mango, for different concentrations of gum (P. juliflora), and the control treatment. The values of apparent viscosity and turbidity in the elaborated nectars, present a positive and high significant correlation (r = 0.94). On the other hand, the gum of P. juliflora contributes to provide an excellent sensory characteristic to the nectars elaborated. The best texture observed in the treatment corresponding to the highest concentration of gum tested (0.30%). This investigation demonstrated the functionality of the Prosopis juliflora gum, as additive in the preparation of nectars of fruit of low caloric content.